Strategies for success in musical theatre a guide for music directors in school, college, and community theatre - Marshall, Herbert D. (Oxford University Press, 2016)
In "Strategies for Success in Musical Theatre", veteran musical director and teacher Herbert Marshall provides an essential how-to guide for teachers or community members who find themselves in charge of music directing a show. Stepping off the podium, Marshall offers practical and often humorous real-world advice on managing auditions; organizing rehearsals; working with a choir, choreographer, and leads; how to run a sitzprobe, a technical rehearsal, and a dress rehearsal; how to manage the cast and crew energy for a successful opening night; and ways to end the experience on a high note for all involved. Throughout the book, Marshall emphasizes the importance of learning through performance and the beauty of a group united in a common goal. In doing so, he turns what can appear as a never-ending list of tasks and demand for specialized knowledge into a manageable, educational, and ultimately engaging and fun experience for all. Because the techniques in Marshall's book have been thoroughly workshopped and classroom tested, they are based in proven pedagogy and will be of particular use for the music director in acting as a teaching director: someone imparting theatrical knowledge to his or her cast and production staff. Marshall provides both extended and abbreviated timelines, flexible to fit any director's needs.